Prognostic Significance of Sarcopenia With Inflammation in Patients With Head and Neck Cancer Who Underwent Definitive Chemoradiotherapy - Cho, Yeona; Kim, Jun Won; Keum, Ki Chang; Lee, Chang Geol; Jeung, Hei Cheul; Lee, Ik Jae (Frontiers in Oncology, 2018)
Purpose: With growing evidence that inflammation and low muscularity play a role in the survival of cancer patients, we evaluated the prognostic implications of sarcopenia with systemic inflammation in patients who underwent definitive chemoradiotherapy (CCRT) for locally advanced head and neck cancer. Materials and Methods: We analyzed 221 patients with head and neck cancer who received definitive CCRT between 2006 and 2015. The skeletal muscle area was measured using a single computed tomography image slice at the level of the third lumbar vertebra (L3). Sarcopenia was defined as an L3 muscle index of <49 cm2/m2 for men and <31 cm2/m2 for women. Results: Patients with sarcopenia (n = 106) exhibited higher neutrophil/lymphocyte ratios (NLRs) than those without (n = 115); the former also had an inferior 3-year overall survival (OS) rate (62%) than the latter (76%, p = 0.037). Among patients with sarcopenia, those who also had high NLRs (n = 51) showed significantly poorer OS and progression-free survival (PFS). In the multivariate analysis, sarcopenia plus a high NLR remained the most significant predictor of poor OS and PFS. Patients with sarcopenia required more frequent interruption of RT; patients whose RT was interrupted for ≥5 days showed inferior disease control and OS. Conclusions: Sarcopenia accompanied by systemic inflammation at initial diagnosis is associated with significantly inferior OS and PFS. Additionally, patients with sarcopenia required RT interruption more frequently. Intensive nutritional support and additional treatment methods are required for these patients while undergoing RT.